The limits of the similarity between the Derridean and the Rabbinic conception of language - Rosàs Tosas, Mar (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
Jacques Derrida, like other contemporary theoreticians, turns several times to Jewish thinkers and categories when formulating his own understanding of text and language. Sometimes it seems like just an analogy, but other times he does it explicitly. This has given rise to several attempts of appropriation on behalf of Judaism. Susan Handelman (1982), Geoffrey H. Hartman and Sanford Budick (1986), Beth Sharon Ash (1987), Sanford L. Drob (1997; 2006), Hélène Cixous (2001), Elliot R. Wolfson (2002), Moshe Idel (2003), Bettina Bergo, Joseph Cohen and Raphael Zagury-Orly (2007) —among others— have tried to show the similarity between the Derridean and Jewish concepts of language; some of them even go so far as to claim that the first is a mere modern representation of the Rabbinic Literature and the Kabbalah. In our opinion, these attempts of appropriation are excessive. Thus, our goal is to explore the analogy between the Derridean understanding of language and the Jewish counterpart at stake in Rabbinic and Kabbalistic literature, in order to show, ultimately, the irreducible specificity of the former.